Ultrasound diagnosis of Achilles tendon pathology in runners. Issue 4 (December 1987) - Maffulli, N; Regine, R; Angelillo, M; Capasso, G; Filice, S
Abstract : The great upsurge in popularity of running activities has increased the number of athletes presenting with pathology of the Achilles tendon. A clinical and ultrasonic study was performed on 47 middle and long distance runners referred to the Authors with such problems. The results of this study can be grouped as follows: 1. paratendonitis: enlargement of the antero-posterior diameter of the tendon, and hyperechogenicity of Kager's triangle; 2. tendonitis (with or without paratendonitis): thickening of the tendon, with the presence of degenerative nodules; 3. enthesopathy: thickening of the distal part of the tendon, enlargement of the hypoechogenic area behind the tendon itself and microcalcification.